The Influence Of Profit Persistence, Sales Growth, Operating Cycle And Tax Allocation Between Period On Profit Quality: (Empirical Study of Mining Sector Companies Listed on the Indonesian Stock Exchange for the 2019-2023 Period) - Syahrul Syarifudin; Najmudin Najmudin (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to empirically examine the effect of earnings persistence, sales growth, operating cycle and inter-period tax allocation on earnings quality. This research was conducted because there are still many companies that have a low earnings quality value. The research method used in this research is descriptive and verification method. The population in this study are the financial reports of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. In this study, a sample of 20 mining sector companies met the purposive sampling criteria. The type of data used in this research is quantitative data and the data source is secondary data. The data analysis model used is panel data regression analysis and the model chosen is the fixed effect model using Eviews 9. To test the hypothesis using the F test and t test. Based on the results of the F test, it shows that the magnitude of earnings persistence, sales growth, operating cycle and inter-period tax allocation together have a significant effect on earnings quality. As for the results of the t test, earnings persistence has a positive and significant effect on earnings quality, sales growth has a positive and significant effect on earnings quality, the operating cycle has a positive and significant effect on earnings quality, and inter-period tax allocation has a negative and significant effect on earnings quality.